Performance Enhancement of Flux Switching Motor for Electric Vehicle Applications: An Overview - Jawad Faiz; Majid Maktobian (IET Electrical Systems in Transportation)
As the reduction of greenhouse gas emissions becomes crucial, electric vehicles (EVs) are expected to enter the market extensively in the coming years. The efficiency of the electrical motor used in EVs plays a significant role in their overall performance. This paper explores the flux switching motor (FSM) and its applications in EVs. The FSM is compared to other electrical motors, highlighting its potential as a suitable choice for EV traction. Various configurations and techniques are reviewed to enhance the performance of FSMs, including magnetic materials, torque ripple alleviation, and magnetic flux weakening. The advantages and disadvantages of these methods are discussed, providing valuable insights for designing FSMs for EVs. Generally, EV traction requires high torque density and high power density electrical motor. To achieve these goals, high electric and magnetic loading must be considered in design stage of the motor. Application of the FSM may be one of the appropriate option. For many reasons, three-phase FSM is preferred. Considering the base speed of machine in the EV and high electric loading, the FSM with 12 stator teeth and 10 rotor teeth may be the most appropriate choice in which the stator core is oriented and rotor core is nonoriented iron. To enhance the torque density and applied flux weakening method, combination of Nd and Al–Ni–Co magnets is preferred.